Penerapan Strategi Branding Produk Stick Ubi sebagai Oleh-oleh Khas Desa Renah Alai Kecamatan Jangkat Kabupaten Merangin - Hardiani Hardiani; Zulfanetti; Dwi Hastuti; Erni Achmad; Purwaka Hari Prihanto (WIDA Publishing, 2022)
The majority of MSMEs do not understand the value of branding in maintaining the sustainability of their business in the future. This is because most MSME businesses focus solely on sales and ignore branding. Furthermore, a lack of awareness of the importance of branding affects a product’s drop in demand. Additionally, the branding strategy must be aligned with the marketing communication plan in order to maximize brand awareness and ensure that people understand how branding can increase consumer confidence in a product. The following methods of community service are utilized to accomplish PPM goals: 1) Group development from industrial society, 2) Persuasive, 3) Educational, 4) Participatory, and 5) Normative based on norms and culture as well as the community’s local potential. The article addressed issues specific to the development of promotions for increasing sweet potato stick marketing through the 2021 PPM. The implementation involved the younger generation in product development through branding strategies that are in line with tourism development, economic development, and sustainable technology improvement.